2
$\begingroup$

I was looking through wiki's treatment on the title topic in https://en.wikipedia.org/wiki/Random_variable and am completely stumped on this particular section:

enter image description here

There are several specifics that elude me.

  • How is the following progression derived

$$Y = \log(1 + e^{-X}) \Longrightarrow F_Y(y) = \Pr( \log(1+e^{-X}) \le y )$$

and then the next step

$$\Pr( \log(1+e^{-X}) \le y) = \Pr( X \ge -\log(e^y - 1) )$$

Thx for filling in the blanks.

$\endgroup$
  • 1
    $\begingroup$ Hint: By definition, for each real number $\alpha$, the value of tthe CDF $F_Y$ at $\alpha$, usually expressed as $F_Y(\alpha)$, equals the probability that $Y$ is no larger than $\alpha$. So, knowing this, can you figure out for yourself why the implication $$Y = \log(1 + e^{-X}) \Longrightarrow F_Y(y) = \Pr(Y \leq y) = \Pr( \log(1+e^{-X}) \le y )$$ holds?? $\endgroup$ – Dilip Sarwate Jun 15 at 20:28
  • $\begingroup$ Yes - ok i see that. $\endgroup$ – javadba Jun 16 at 8:17
2
$\begingroup$

Introduction. The so-called "CDF method" is one way to find the distribution of a the transformation $Y = g(X)$ of a random variable $X$ with a known CDF. Let's look at a simpler example first: Suppose $X \sim \mathsf{Univ}(0,1)$ and find the CDF of $Y = g(X) = \sqrt{X}.$ The support of $X$ is $(0,1)$ and it is clear that the support of $Y$ will also be $(0,1).$

The CDF of $X$ is $F_X(x) = x,$ for $x \in (0,1).$ Then the CDF of $Y$ is $$P(Y \le y) = P(g(X) \le y) = P(\sqrt{X} \le y) = P(X \le y^2) = y^2,$$ for $y \in (0,1).$ The last step uses $F_X(x) = P(X \le x) = x,$ where $y^2 = x.$ Thus the PDF of $Y$ is $f_Y(y) = F_Y^\prime(y) = dy^2/dy = 2y,$ which we recognize as the PDF of $\mathsf{Beta}(2,1).$

Illustrating this with a random sample of $n = 10^5$ observations $X_i$ from $\mathsf{Unif}(0,1),$ we have the following results (in R):

set.seed(615)
x = runif(10^5, 0, 1);  y = sqrt(x)
par(mfrow=c(1,2))
 hist(x, prob=T, col="skyblue2", main="X ~ UNIF(0,1)")
  curve(dunif(x, 0, 1), add=T, n=10001, lwd=2, col="brown")
 hist(y, prob=T, col="skyblue2", main="Y ~ BETA(2,1)")
  curve(dbeta(x, 2, 1), add=T, n=10001, lwd=2, col="brown")
par(mfrow=c(1,1))

enter image description here

Your Question. Now let's do a similar procedure for $X$ with CDF $F_X(x) = P(X \le x) = (1 + e^{-x})^{-\theta},$ for $\theta > 0$ and the transformation $Y = g(X) = \log(1+e^{-X}),$ which has support $(0, \infty).$

Using the CDF method again, we have:

$$F_Y(y) = P(Y\le y) = P(\log(1 + e^{-X})\le y) = P(1+e^{-X} \le e^y)\\ =P(e^{-X} \le e^y - 1) = P(-X \le \log(e^y -1))\\ = P(X \ge -\log(e^y -1)) = \cdots,$$

So, $F_y(y) = 1-e^{-\theta y},$ for $y > 0,$ as claimed.

We illustrate with a random sample of $n = 10^5$ observations from the original logistic distribution with $\theta = 1.$ This distribution can be sampled in terms of standard uniform distributions as shown in the R code; see Wikipedia, second bullet under Related Distributions.

set.seed(2019)
u = runif(10^5);  x = log(u) - log(1-u)
y = log(1 + exp(-x))
par(mfrow=c(1,2))
 hist(x, prob=T, br=30, ylim=c(0,.25),  col="skyblue2", main="Logistic")
  curve(exp(-x)/(1+exp(-x))^2, add=T, lwd=2, col="brown")
 hist(y, prob=T, ylim=c(0,1), col="skyblue2", main="Exponential")
  curve(dexp(x,1), add=T, lwd=2, n=10001, col="brown")
par(mfrow=c(1,1))

enter image description here

$\endgroup$
2
$\begingroup$

\begin{align} & \log(1+e^{-X}) \le y \\[12pt] & 1+e^{-X} \le e^y \\ & \text{since } \log \text{ and } \exp \\ & \text{are increasing functions} \\[12pt] & e^{-X} \le e^y - 1 \\[12pt] & {-X} \le \log(e^y - 1) \\ & \text{since } \log \text{ and } \exp \\ & \text{are increasing functions} \\[12pt] & X \ge -\log(e^y - 1) \end{align}

$\endgroup$
1
$\begingroup$

Question 1:

By definition, FY(y) = Pr(Y<=y)

And because we know that Y=log(1+e^−X)

Then FY(y) = Pr(log(1+e^−X) <= y)

Question 2:

All they're doing there is starting with log(1+e^−X)≤y

and simply solving for X

which entails, first doing e^ on both sides:

1+e^−X ≤ e^y

then sending the 1 to the right:

e^−X ≤ e^y - 1

then doing log on both sides:

−X ≤ log(e^y - 1)

and finally multiplying both sides by -1, which changes the direction of the ≤

So you end up with:

X≥−log(e^y−1)

which is what they got

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.